On the distribution of some ordered variables. Issue 7 (2nd April 2016) - Nadarajah, Saralees; Chan, Stephen; Afuecheta, Emmanuel
Abstract: Motivated by a recent article published by Adam and Tawn, we characterize the distribution of two random variables X, Y ordered linearly like X < Y . We suppose that the random variables follow a bivariate extreme value distribution.